Social and Economic Conditions of The United States of America During the Civil War 1861-1865 - Pertiwi, Ayu; Gusriandari, Wahyu; Saputro, Guntur Eko (Journal of Social Work and Science Education, 2023)
In the long history of struggle of the Indonesian nation, at a certain period of time during the Dutch colonization, there was a war that made colonialists experience difficulties. The war was caused by the resistance of a Javanese nobleman named Prince Diponegoro, this war was called the Diponegoro War or known as the Java War. Because of the unprecedented amount of popular resistance, the losses suffered by both the colonizers and the Javanese people were very large, both human and material casualties, this was closely related to economic conditions during the war and after the end of the war. This paper aims to analyze and describe the consequences of the war that occurred at that time on the Dutch colonial as well as on the Javanese people themselves, from an economic aspect. Research through a qualitative approach with a descriptive method, namely literature study and usually historical research using heuristic methods. The results of the study stated that the consequences of the Java War were very significant in affecting the lives of Javanese people and the Dutch colonial after the war.